6. The Fampridine Upper Limb Study: Baseline clinical and electrophysiological data. Issue 3 (March 2016) - Simpson, Marion; Dimovitis, Joanne; Heriot, Elise; Bardsley, Belinda; Carey, Leeanne; Yiannikas, Con; Macdonell, Richard
Abstract : Aim: To describe initial clinical and electrophysiological results from the Fampridine Upper Limb Study, conducted in patients with Multiple Sclerosis (MS) and upper limb impairment. Methods: This randomised, double-blinded placebo controlled trial of modified-release fampridine comprises three groups: patients on drug, patients on placebo and healthy controls. Baseline assessments conducted prior to initiation of drug (fampridine-MR 10 mg bd) or placebo included the following clinical tests: 9-hole peg test, manual grip strength, sensory discrimination capacity, visual acuity & contrast sensitivity, Fatigue Impact Scale score. Baseline electrophysiological tests included the following: visual evoked potential latency and amplitude, somatosensory evoked potential, median motor and sensory nerve conduction studies & F-waves, resting motor threshold, MEP latency, paired-pulse transcranial magnetic stimulation, MEP recruitment curves. Comparisons were made at baseline between MS patients and controls, and between patients with different MS subtypes (RRMS, PPMS, SPMS). Correlations were made between clinical and electrophysiological measures at baseline. Results: 40 patients (60% female, median age 52 years) with MS and upper limb impairment and 20 healthy controls (60% female, median age 53 years) were studied. Of the patients, 9 had RRMS, 18 had SPMS and 13 had PPMS. The results of clinical measures of hand function (9-hole peg test, manual grip strength) and electrophysiological tests of nervous system function (VEP latency & amplitude, SSEP latency, MEP latency, resting motor threshold, MEP recruitment and PPTMS) are reported and compared between patients and controls and between patients with different subtypes of MS disease course. Conclusion: Evoked potentials and TMS measures differ between MS patients and healthy controls, with observable differences between patients with different subtypes of MS. Such electrophysiological markers may represent useful surrogate markers in clinical trials of symptomatic and disease-modifying therapies for MS.